Intraoral inverted 'L' osteotomy of the mandibular ramus - João Luiz Carlini; Mauricio Romanosvki; Tuanny Nascimento (Elsevier, 2021)
In corrections of dentofacial deformities where the mandible is the problem, the inverted 'L' osteotomy may be a good option in specific cases, such as large mandibular advancements, condylar alterations, reoperations of the mandible, to increase the posterior facial height. This technique was not much-used because the procedure used to be performed extraorally, leaving undesirable scars. We will describe the use of the technique via intraoral access, with allogeneic grafts and use of rigid internal fixation.